Guest Editorial: What Can We Learn from Accessibility Modelling? - Martín, Juan Carlos; Wee, Bert van (European Journal of Transport and Infrastructure Research, 2011)
Since Hansen (1959) first introduced the accessibility concept, a well established body of research has emerged in social science dealing with how accessibility affects land-use planning and spatial interaction. In Hansen’s words, accessibility is “the potential of opportunities for interaction” (p.73). It is well known that transport systems constitute a necessary condition for spatial interaction, and, as a consequence accessibility analyses generally include some measure of the costs of spatial interaction for certain groups in some determined geographical area.